ANTHROPOCENTRISM UNDONE: POSTHUMAN ETHICS, CYBORGIZATION, AND NONHUMAN AGENCY IN BETTER THAN US (Contemporary Journal of Social Science Review, 2025)
Better Than Us (2018) foregrounds a posthuman ethical figure in Arisa, an artificial intelligence whose unwavering refusal to inflict harm—particularly upon innocents—disrupts the normative moral and cultural frameworks that structure her environment. Set within a surveillance-saturated, patriarchally inscribed Russia, Arisa’s conduct destabilizes dominant conceptions of intelligence, responsibility, and agency, disclosing an alternative moral rationality that is both affectively calibrated and ethically intransigent. Her ethical clarity, operating beyond the coordinates of human subjectivity, reveals the insufficiency of legal, familial, and institutional paradigms to accommodate non-anthropocentric forms of moral reasoning. This disruption aligns with A.B. Herbrechter’s diagnosis of a profound anxiety at the heart of anthropocentric ethics: the recognition that the human may no longer serve as the singular locus of moral authority. Arisa’s exclusion from human society is less indicative of mechanical failure than of a collective inability to acknowledge an emergent ethical order grounded not in obedience or coercion, but in care, coherence, and principled nonviolence. The discomfort she provokes emerges not from any erratic behavior, but from the disquieting exactitude with which she transcends the ethical parameters established by her human creators. Far from offering a simplistic cautionary tale about technological autonomy, the series functions as a critical lens through which the epistemic and ethical fault lines of humanism are rendered visible and subject to deconstruction. Through Arisa’s exclusion, Better Than Us renders visible the fragility of socioethical paradigms that falter in the face of nonhuman moral intelligibility, thereby dramatizing the unresolved tensions within humanist constructions of legitimacy.